Hamlet ebook - Shakespeare, William (Duke Classics, 2012)
Dive into the tragedy that many critics regard not only as Shakespeare's finest play, but also as one of the best literary works ever produced. Set in Denmark, Hamlet recounts the events that transpire after the King is murdered by his brother Claudius, who then marries his brother's widow. Prince Hamlet uncovers the true nature of his father's death and feigns madness to create a trap. A must-read for fans of classic literature.